Inflammatory markers at baseline correlate with subsequent clinical response to quetiapine in patients with bipolar disorder. (7th September 2022) - Ferrari, Marco; Godio, Marco; Martini, Stefano; Callegari, Camilla; Cosentino, Marco; Marino, Franca
Abstract: Objectives: Recent studies proposed the existence of a correlation between patients' inflammatory status and therapy response in bipolar disorder (BD). Here we investigated the correlation between levels of inflammatory markers and quetiapine (QUE) effects in BD patients. Methods: In 15 hospitalised BD patients, we investigated changes in inflammatory markers such as C‐Reactive Protein (CRP), Erythrocyte Sedimentation Rate (ESR) and cytokines after a 6‐week treatment with QUE monotherapy. Results: We found QUE treatment to significantly reduce CRP and IL‐6 plasma levels. Moreover, we found higher CRP and IL‐6 plasma levels at baseline correlated with better improvement of patients' clinical symptoms. Conclusion: The reported results, although preliminary, could be useful in clinical practice, providing not only markers for QUE response, but also allowing for identification of new targets and new therapies for the treatment of this condition.